Effect of construction work conditions on safety outcomes: Construction safety resilience as a mediator. - Hu, Zhen; Li, Siyi; He, Changquan; Shen, Yuzhong; Li, Siyuan; Zhong, Heng (Work, 2025)
Background: Work conditions are critical for construction workers' personal health and project safety performance. However, few studies have explored the effect of construction work conditions on safety outcomes from a systematic perspective. Objective: This study examined the relationship between construction work conditions (CWCs, including high temperature, rainy day, nighttime, and low temperature) and safety outcomes (including physical symptom, psychological symptom, and unsafe event), while construction safety resilience (CSR) performing as a mediator. Methods: The techniques of structural equation modeling were used with 762 survey data collected from the Chinese construction industry to empirically test the structural equation model. Results: The results show that CWCs directly affected CSR, and indirectly impacted safety outcomes through CSR. Meanwhile, CSR directly reduced physical and psychological symptoms of construction workers, and indirectly cut down unsafe events through physical and psychological symptoms, respectively. Further, CSR completely mediated the relationship between CWCs and safety outcomes. Conclusions: There exist complex relationships among construction work conditions, safety resilience and safety outcomes. The results also remind the safety managers to improve construction work conditions from the perspective of safety resilience, and initiate a resilient safety management system integrating physical, psychological, and environmental factors, thus enhancing safety outcomes of construction projects.